ANALISIS PENGUNGKAPAN DAN DAMPAK PENERAPAN CORPORATE SOCIAL RESPONSIBILTY DI PT BANK PEMBANGUNAN DAERAH BALI - Hiwa Sawaka K, I Gst Ngr; Asri Dwija Putri, I Gusti Ayu Made (E-Jurnal Akuntansi, 2016)
CSR is the responsibility of the company in improving social inequality and environmental damage caused by the company's operational activities. Corporate responsibility should be based on the triple bottom lines. This study aims to determine the disclosure of the application of CSR BPD Bali and its impact. This study used a qualitative descriptive data analysis techniques. The data used in this study are secondary and primary. Secondary data in this study is the annual report that is downloaded directly www.bpdbali.co.id and primary data in the study were interviews with staff CSR BPD Bali. Discussion results showed that: 1) the disclosure of the application of CSR undertaken by PT BPD Bali has to be said either 2) Strong Basis BPD Bali implement CSR activities is a legal basis. 3) The impact of the adoption of this CSR is the impact of the financial and non-financial impact.
Keywords: CSR disclosure, basic application, CSR impact